Long-term HIV Pre-exposure Prophylaxis Trajectories Among Racial & Ethnic Minority Patients: Short, Declining, & Sustained Adherence. (1st February 2022) - Pyra, Maria; Brewer, Russell; Rusie, Laura; Kline, Jeanelle; Willis, India; Schneider, John
Abstract : Background: HIV pre-exposure prophylaxis (PrEP) requires continued use at an effective dosage to reduce HIV incidence. Data suggest early PrEP drop-off among many populations. We sought to describe PrEP use over the first year among racial and ethnic minority patients in the US. Setting: Racial and ethnic minority patients initiating PrEP at a federally qualified health center in Chicago, IL. Methods: Using electronic health records, we determined the adherence (≥6 weekly doses) trajectories over the first year of PrEP use and compared baseline and time-varying patient characteristics. Results: From 2159 patients, we identified 3 PrEP use trajectories. Sustained use was the most common (40%) trajectory, followed by short use (30%) and declining use (29%). In adjusted models, younger age, Black race, as well as gender, sexual orientation, insurance status at baseline, and neighborhood were associated with trajectory assignment; within some trajectories, insurance status during follow-up was associated with odds of monthly adherence (≥6 weekly doses). Conclusion: Among racial and ethnic minorities, a plurality achieved sustained PrEP persistence. Access to clinics, insurance, and intersectional stigmas may be modifiable barriers to effective PrEP persistence; in addition, focus on younger users and beyond gay, cismale populations are needed. Abstract : Supplemental Digital Content is Available in the Text.